Achieving single-molecule-based multi-color emissions by the regulations of intramolecular proton transfer and interphase transformation. (February 2023) - Zhao, Wenyang; Ding, Zeyang; Li, Bao; Chen, Chunrong; Zhang, Houyu; Jiang, Shimei
Abstract: Endowing fluorescent materials with multi-color tunable properties in a single-component system remains challenging. Herein, a series of salicylaldehyde Schiff base derivatives with different lengths of alkoxy chains (NPA-n, n = 1, 4, 8, 12) are synthesized. All the derivatives exhibit wide-range tunable emissions through intramolecular proton transfer and interphase transformation. In the solution state, NPA-n derivatives emit blue (E*) and green (K*) emissions, produced by the excited-state intramolecular proton transfer (ESIPT) effect by controlling the polarity of solvents. In the solid state, J- type aggregation results in red-shifted emissions. Polymorphic emissions of NPA-12 with yellow and red, produced by ground-state intramolecular proton transfer (GSIPT) effect, are realized by controlling the aggregated degree. Therefore, NPA-12 presents color tunable emissions covering fully visible spectrum (about 183 nm), including blue, green, yellow and red. The as-obtained system is further applied to thermochromic and mechanochromic aspects. The research provides a strategy to construct multi-color fluorophores for diverse applications. Graphical abstract: A dual-state emitting material is achieved owing to the coexistence of planar naphthaldehyde and twisted cyanostilbene groups in a single molecule, which presents multi-color tunable emissions with a wide range (about 183 nm), covering blue, green, yellow and red. Image 1 Highlights: Multi-color emissions covering fully visible spectrum (about 183 nm) are achieved in a single molecule. Efficient emissions in both dispersed and aggregated states are guaranteed with the combination of planar and twisted motifs. A unique ground-state intramolecular proton transfer (GSIPT) effect is realized and controlled by the aggregated degree. The system shows high-contrast thermochromic and mechanochromic properties in aggregated states.